2014
DOI: 10.1186/1471-2458-14-61
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of the environment, physical activity, and screen time among young children and their parents

Abstract: BackgroundTo develop evidence-based interventions promoting healthy active lifestyles among young children and their parents, a greater understanding is needed of the correlates of physical activity and screen time in these dyads. Physical environment features within neighborhoods may have important influences on both children and their parents. The purpose of this study was to examine the associations between several features of the physical environment with physical activity and screen time among 511 young c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 37 publications
2
52
2
3
Order By: Relevance
“…The results found that screen time in the three intervention groups, which were above six hours for both weekdays and weekend days, were much greater than the limits of < 2 hours indicated in the literature 19 . Nevertheless, results greater than those indicated here were found in other studies recently performed [20][21][22] .…”
Section: Resultscontrasting
confidence: 84%
“…The results found that screen time in the three intervention groups, which were above six hours for both weekdays and weekend days, were much greater than the limits of < 2 hours indicated in the literature 19 . Nevertheless, results greater than those indicated here were found in other studies recently performed [20][21][22] .…”
Section: Resultscontrasting
confidence: 84%
“…Parent’s screen-time is known to influence children’s screen-time [16] and there is evidence that homes where there are rules on children’s use of screen devices for recreational purposes provide some protection against overweight and obesity [17]. …”
Section: Introductionmentioning
confidence: 99%
“…It is also important for young adolescents going through puberty to engage in a mix of aerobic, and muscle‐ and bone‐strengthening activities as bone mass gains peak during this stage . However, even with all the benefits linked to PA, children are not as active as recommended . PA, as measured by steps per day, declines for boys and girls, from 6 years old onward (from 14,000 to 11,000 for boys and 13,000 to 8000 for girls) .…”
Section: Differences Between Latino and White Childrenmentioning
confidence: 99%